Structural insights into human polyspecific organic anion transporters OAT1 and OAT4 - Wei Zhang; Youfu Chu; Ziyang Shan; Huihui Liu; Xuemei Yang; Jing Nan; Feiwen Wei; Yanqing Zhang (Cell Reports)
Summary: Organic anion transporters (OATs) play a critical role in the transport of organic anions. OAT1, located in the kidney, is essential for the transport of organic anion drugs and metabolites, while OAT4 facilitates absorption processes in the kidney and placenta. Here, we resolved the cryo-electron microscopy structures of human OAT1 in its apo form and bound to probenecid, adefovir, cefazolin, and para-aminohippuric acid (PAH), as well as human OAT4 in its apo form and in complex with dehydroepiandrosterone sulfate (DHEAS). We observed a shared ligand-binding mode in OAT1 that appears to be common within the SLC22 family, characterized by two aromatic residues clamping the ligand and a pair of opposing charged residues that determine ligand orientation. DHEAS in OAT4 exhibits a different binding mode, illustrating the multispecific ligand-binding characteristics of OATs. Our findings provide a framework for drug design and management of drug-drug interactions involving OAT1.